Clustered Regularly Interspaced Short Palindromic Repeats/Cas9 Gene Editing Technique in Xenotransplantation - Naeimi Kararoudi, Meisam; Hejazi, Seyyed S.; Elmas, Ezgi; Hellström, Mats; Naeimi Kararoudi, Maryam; Padma, Arvind M.; Lee, Dean; Dolatshad, Hamid (Frontiers in Immunology, 2018)
Genetically modified pigs have been considered favorable resources in xenotransplantation. Microinjection of randomly integrating transgenes into zygotes, Somatic somatic cell nuclear transfer (SCNT), Homologous homologous recombination (HR), Zinc zinc finger nucleases (ZFN), Transcription activator like effector nucleases (TALENs) and the most recently, Clustered clustered Regularly regularly iInterspaced Short short Palindromic palindromic Repeatsrepeats-Cas9 cas9 (CRISPR/Cas9) are the techniques that have been used to generate these animals. Here we provide an overview of the CRISPR approaches that have been used to modify genes which are vital in improving xenograft survival rate, including viz. CMAH, B4GALNT2, iGb3s, Class I MHC, vWF, C3, and PERVs. Additionally, we will mention the importance of potential candidate genes which could be targeted using CRISPR/Cas9.